HEALTH CARE FOR WOMEN IN THE PREGNANCY-PUERPERIUM CYCLE: EVALUATION OF ACCESSIBILITY IN PRIMARY CARE - Sheila Milena Pessoa dos Santos; Jéssica Oliveira Rodrigues; Lais Vasconcelos Santos; Lara Caline dos Santos Lira; Ueigla Batista da Silva; Laianne Barbosa de Souza (Universidade Federal do Paraná, 2016)
This study aimed to analyze accessibility to the health service of women in the pregnancy-puerperium cycle, in the perception of the female service users. To this end, an exploratory, descriptive study was undertaken, with a qualitative approach, using a semistructured interview for data collection. The population was made up of women who had been, or were, in the pregnancy-puerperium cyclein January 2012 - April 2014. The criteria of saturation was adopted for defining the sample, which reached the number of 29 interviewees. The thematic categorical technique was adopted for analysis of the data. The results showed the existence of various geographical, economic, sociocultural and organizational barriers in the assistance to women in the pregnancy cycleand in the postpartum period. It is possible to note the need for organizational changes which would be reflected in improvement in the quality of the care.